Optimal metabolic regulation along resource stoichiometry gradients. (30th July 2017) - Manzoni, Stefano; Čapek, Petr; Mooshammer, Maria; Lindahl, Björn D.; Richter, Andreas; Šantrůčková, Hana
Abstract: Most heterotrophic organisms feed on substrates that are poor in nutrients compared to their demand, leading to elemental imbalances that may constrain their growth and function. Flexible carbon (C)‐use efficiency (CUE, C used for growth over C taken up) can represent a strategy to reduce elemental imbalances. Here, we argue that metabolic regulation has evolved to maximise the organism growth rate along gradients of nutrient availability and translated this assumption into an optimality model that links CUE to substrate and organism stoichiometry. The optimal CUE is predicted to decrease with increasing substrate C‐to‐nutrient ratio, and increase with nutrient amendment. These predictions are generally confirmed by empirical evidence from a new database of c . 2200 CUE estimates, lending support to the hypothesis that CUE is optimised across levels of organisation (microorganisms and animals), in aquatic and terrestrial systems, and when considering nitrogen or phosphorus as limiting nutrients.